Direct marketing : strategy, planning, execution - Nash, Edward L. (McGraw Hill, 2000)
Introduction. Strategic planning. The marketing plan. Research. Testing. The proposition. "Back-end" marketing. Mail order math. Creative tactics. Copywriting. Art direction. Direct mail formats. Production planning. Mailing lists. Print media. Broadcast media. Broadcast creative. Telemarketing. Fulfillment. Database marketing. Internet marketing. Going global.